Cytokine responses and progression to active tuberculosis in HIV-1-infected Ugandans: a prospective study. - Elliott, A; Hodsdon, W; Kyosiimire, J; Quigley, M; Nakiyingi, J; Namujju, P; Watera, C; French, N; Gilks, C; Dockrell, H; Whitworth, J (2004)
Identifying correlates of immunity or susceptibility to disease promotes understanding of pathogenesis and development of diagnostic tools, treatments, and vaccines. There is evidence that type 1 cytokine responses are associated with protection against tuberculosis, and suppression of type 1, or switching to type 2 responses, with susceptibility, but this has not been studied prospectively. We studied a cohort of 631 HIV-1-infected Ugandan adults. At enrollment we performed whole blood cultures for type 1 (interferon [IFN]-gamma, interleukin [IL]-2) and type 2/immunosuppressive (IL-5, IL-10) responses to mycobacterial antigens (purified protein derivative [PPD] and culture filtrate proteins [CFP]). The incidence of tuberculosis was not associated with IFN-gamma responses, but was higher among participants with IL-2 responses (adjusted rate ratios [RR]: PPD 3.48; CFP 3.99; P < 0.001). For tuberculin skin test-positive participants, high incidence was also associated with an IL-10 response to PPD (adjusted RR 6.24, P = 0.03); for those with a BCG scar, high incidence was associated with positive IL-5 responses (adjusted RRs: PPD 3.64, P = 0.006; CFP 3.44, P = 0.04). The association with IL-2 production may reflect a response to tuberculous infection or to activating disease; the associations with IL-10 and IL-5 are in keeping with the expected role of immunosuppressive or type 2 cytokines.